Patterns of uptake and repair following recasts and prompts in an EFL context: Does feedback explicitness play a role? - Shirani, Reza (Studies in Second Language Learning and Teaching, 2019)
This study sought to examine the effectiveness of two categories of feedback, namely recasts and prompts. Also, the study focused on the relationship between subsets of each feedback type and the extent to which they led to learner uptake and repair in an EFL context. Data were collected through non-participant observations of three intact upper-intermediate EFL classes where 36 hours of interactions among 59 students and three teachers were audiotaped, transcribed, and analyzed in terms of pre-specified coding systems that addressed four different subtypes of prompts – clarification requests, repetitions, elicitations, and metalinguistic clues – and two recast subtypes – explicit and implicit recasts. Data analysis showed that among prompts, clarification requests led to the highest percentage of uptake whereas elicitations were associated with the highest repair percentage. As for recasts, more explicit ones led to higher percentages of uptake and repair. The results of the study may contribute to a more in-depth understanding of the patterns of uptake and repair in an EFL context. The study confirms the role of feedback explicitness in such a context.